(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article the combination of elements of traditional dress of the Surkhandarya region with modern fashion trends is studied within the framework of the Pret-a-Porter de Lux concept. The study analyzes the constructive transformation of national clothes, their adaptation to modern fashion, while preserving their cultural identity. The choice of materials, decorative elements, and the influence of ergonomic design on clothing aesthetics and functionality are discussed. The research results contribute to the development of national fashion, the combination of historical heritage and innovative design approaches, as well as the international recognition of the rich textile culture of Uzbekistan.